'Ageing Playfully': a story of forgetting and remembering. Issue 1 (2nd January 2017) - Escalante, Maria A. Luján; Tsekleves, Emmanuel; Bingley, Amanda; Gradinar, Adrian
ABSTRACT: An increasing interest in exploring how digital innovation could support dementia care has been a leading research responding to e-health movements, from caregiving and medical perspectives. Little research has included perspectives of people with dementia; even fewer are concerned with the emotional side of the research experience per se. The aim of this case study is to open a space for a discussion of the impact that this process has on design researchers engaging in the area of dementia. Grounded in these two overlapping creative spaces, a methodology emerged that focused on adding design value to outcomes and to all stakeholders involved along the process. The Ageing Playfully project explored, through a series of playful workshops, the opportunities available for people with dementia to catalyse imagination and social interaction through co-design. Participating in Ageing Playfully were 12 co-designers with dementia, 2 healthcarers and 4 researchers from Lancaster University working in the areas of design, computer science and health studies. This paper recounts the experience of the design researchers as part of the team and constructs a narrative in which emerging methods together with personal experience are protagonists; a story that offers memories within the forgetful corners of the investigation.